Industrial scale Large Eddy Simulations with adaptive octree meshes using immersogeometric analysis. (1st September 2021) - Saurabh, Kumar; Gao, Boshun; Fernando, Milinda; Xu, Songzhe; Khanwale, Makrand A.; Khara, Biswajit; Hsu, Ming-Chen; Krishnamurthy, Adarsh; Sundar, Hari; Ganapathysubramanian, Baskar
Highlights: Deployed VMS with weak BCs on massively parallel octree-based adaptive meshes. Developed octree parallelization, efficient matrix assembly, and rapid in-out tests. Demonstrated the ability to capture drag crisis without any wall treatment. Demonstrated scalability of the framework up to O ( 32 K ) processors. Deployed for industrial scale study of the platooning effect of semi-trucks. Abstract: We present a variant of the immersed boundary method integrated with octree meshes for highly efficient and accurate Large Eddy Simulations (LES) of flows around complex geometries. We demonstrate the scalability of the proposed method up to O ( 32 K ) processors. This is achieved by (a) rapid in-out tests; (b) adaptive quadrature for an accurate evaluation of forces; (c) tensorized evaluation during matrix assembly. We showcase this method on two non-trivial applications: accurately computing the drag coefficient of a sphere across Reynolds numbers 1 − 10 6 encompassing the drag crisis regime; simulating flow features across a semi-truck for investigating the effect of platooning on efficiency.